2018
DOI: 10.1080/10494820.2018.1470986
|View full text |Cite
|
Sign up to set email alerts
|

Returning after taking a break in online distance higher education: from intention to effective re-enrollment

Abstract: Dropout is a major concern in higher education, especially in distance education, which experiences higher dropout rates. Taking into account that the flexibility of online higher education allows students to opt for periods of non-enrolment (i.e. breaks), an approach is adopted at a programme level that analyses the intention to continue of those students that have not enrolled in the second semester. Thanks to this longitudinal analysis, re-enrolment intention can be compared with the effective restart of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 67 publications
2
17
0
1
Order By: Relevance
“…There are scores of theories that studied motivators of behavioral intention (e.g. Grau-Valldosera et al, 2019;Guo et al, 2016;Kim, 2019;Kim & Kim, 2017;Yang et al, 2017;Zhou, 2017;Zhu et al, 2020). Among them, the Theory of Planned Behavior (TPB; Fishbein & Ajzen, 1975) and the Technology Acceptance Model (TAM; Davis, 1986) provided a theoretical framework allowing this study to understand what motivates to develop RTOC participation intention.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…There are scores of theories that studied motivators of behavioral intention (e.g. Grau-Valldosera et al, 2019;Guo et al, 2016;Kim, 2019;Kim & Kim, 2017;Yang et al, 2017;Zhou, 2017;Zhu et al, 2020). Among them, the Theory of Planned Behavior (TPB; Fishbein & Ajzen, 1975) and the Technology Acceptance Model (TAM; Davis, 1986) provided a theoretical framework allowing this study to understand what motivates to develop RTOC participation intention.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…In the specific case of online education, the research has not reached conclusive results. While some research has indicated that there is no significant association between gender and dropout rates (Patterson & McFadden, 2009;Tello, 2007;Wojciechowski, 2004), other studies have pointed to a higher probability of dropout among men (Packham et al, 2004), and a greater likelihood of women continuing (Grau-Valldosera et al, 2019) and obtaining degrees in specific fields, particularly in those where they are a small minority (Callejo Gallego, 2001). In contrast, some research has suggested a pattern of higher dropout risk among women regardless of the type of studies undertaken or previous grades obtained (Stoessel et al, 2015).…”
Section: Trajectories In Higher Education Non-traditional Students and University Typementioning
confidence: 99%
“…The data from this study show that during the confinement decreed on 14 March 2020 [7], adult education was redirected towards online and flexible learning [17] to try to overcome inequalities and the digital divide [20,21]. However, the lack of generalization of telematic teaching [79] means that the educational community, which includes the education of adults in a non-formal environment, has had to improvise this emergency teaching remotely [28], sometimes continuing its teaching with mobile and WhatsApp, or via email. That is to say, this leap from face-to-face teaching to distance work [80][81][82], to respond to the needs of students without previous experience and without a planned operation [29], translates into dispersion and complementary use of the means and tools and applications that allow the continuity of the activity, such as the telephone, WhatsApp, Jitsi, Zoom, Skype, and email, according to the characteristics and means available to the students and the teachers themselves.…”
Section: Discussionmentioning
confidence: 99%
“…That is, we are facing an unprecedented situation in education [24], a methodological change whose flexibility lies in ubiquity, producing a change in how, when, and where student learning occurs [25]; where people are active agents of their own learning, a factor that, together with technological mediation, given their indisputable social and collective value [26], can provide greater access to lifelong high-quality learning experiences [27]. However, at the same time, the difficulties of the digital divide, distance education [28], as well as the lack of systematisation by institutions are evident. This is the reason why, during confinement, an emergency remote teaching [29] has been continuing with the same content and methods lacking an optimal design and implementation [29], where the digital divide and other gaps have possibly been widened [30].…”
Section: Introductionmentioning
confidence: 99%